Climate Change and Kuznets Curve: Portuguese Experience - Nuno Carlos Leit\~ao (Fondazione Eni Enrico Mattei (FEEM), 2018)
The climate change has inspired the interest of the academic community in the most diverse areas of knowledge. This study tests and revisited the environmental Kuznets curve assumptions for Portugal. The econometric strategy used in this research is time series (ARIMA model, OLS estimator, ARCH regression, VAR model, and Granger causality) for the time period 1980-2013.The econometric results show that the income per capita and squared income per capita are according to the expected signs, i.e. a positive impact of income per capita on carbon dioxide emissions, and a negative effect of squared income per capita on carbon dioxide emissions. The empirical study also demonstrates that Portugal presents a dependence on energy consumption. The openness trade and foreign direct investment are negatively correlated with carbon dioxide emissions.
Keywords: C50; Q43; Q53; 330; Environmental Kuznets Curve; Climate Change; Time Series and Openness Trade